Identification of images of objects obtained in low light conditions using neural network technologies - Lin, K.; Balukho, I. N.; Zhukova, M. N.; Kolchevsky, N. N. (БНТУ, 2025)
The possibilities of artificial intelligence methods, in particular multilayer neural networks, are being studied for object recognition in X-ray images obtained at low photon fluxes. The achieved accuracy level (81–90 %) allows such approaches to be considered promising for further integration into intelligent data processing systems for medical and industrial radiography.